2007
DOI: 10.21704/rea.v6i1-2.350
|View full text |Cite
|
Sign up to set email alerts
|

Assemblages of Bird and Mammal Communities in Two Major Ecological Units of the Andean Highland Plateau of Southern Peru

Abstract: Grasslands in the Andean highlands plateau of southern Peru have been considered as a single and homogeneous dry habitat also known as Puna. However, in some regions, a highest rainfall regimen is found, and the name of wet puna has begun to be used by some authors. Since no studies have been carrying out specifically to test if dry and wet puna are different ecological units, we chose two representative localities of each one of these habitat to evaluate assemblages of bird and mammal communities and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Phrygilus alaudinus observado en Puno a 4565 m (Gibbons et al, 2011). Otro estudio efectuado por Ramírez et al (2007) Fjeldså & Kessler (1996, 2004, citado por Martínez & Villarte (2009). Un tipo adicional de desplazamientos altitudinales no definidos concierne a las aves residentes que van de un lugar a otro en el Altiplano en busca de alimento, especialmente en la época de sequía; ellas llegan a diferentes lagunas, de acuerdo a la disponibilidad y abundancia de sus alimentos preferidos, y cuya ocurrencia depende en general de características ambientales favorables (Ramírez et al, 2007).…”
Section: Residentesunclassified
See 1 more Smart Citation
“…Phrygilus alaudinus observado en Puno a 4565 m (Gibbons et al, 2011). Otro estudio efectuado por Ramírez et al (2007) Fjeldså & Kessler (1996, 2004, citado por Martínez & Villarte (2009). Un tipo adicional de desplazamientos altitudinales no definidos concierne a las aves residentes que van de un lugar a otro en el Altiplano en busca de alimento, especialmente en la época de sequía; ellas llegan a diferentes lagunas, de acuerdo a la disponibilidad y abundancia de sus alimentos preferidos, y cuya ocurrencia depende en general de características ambientales favorables (Ramírez et al, 2007).…”
Section: Residentesunclassified
“…Otro estudio efectuado por Ramírez et al (2007) Fjeldså & Kessler (1996, 2004, citado por Martínez & Villarte (2009). Un tipo adicional de desplazamientos altitudinales no definidos concierne a las aves residentes que van de un lugar a otro en el Altiplano en busca de alimento, especialmente en la época de sequía; ellas llegan a diferentes lagunas, de acuerdo a la disponibilidad y abundancia de sus alimentos preferidos, y cuya ocurrencia depende en general de características ambientales favorables (Ramírez et al, 2007). Estos desplazamientos han sido observados desde 1896 en que Kalinowski llega a Puno, a los alrededores del Lago Titicaca y realiza recorridos, sobre la ruta de Moquegua hasta Titire y al lago de Pahara, en donde encontró a Rhea darwini, Phoenicoparrus jamesi, y Recurvirostra andina, aves que, en ese entonces, aún no se conocían desde el Perú (Franke, 2007).…”
Section: Residentesunclassified
“…For example, Terborgh (1977) while studying bird diversity along an altitudinal gradient in Vilcabamba in Peru, found that nectarivorous birds (hummingbirds and flowerpiercers) accounted for nearly 50% of the netted individuals near timberline. While in the high Andes forest of Cuzco, Ramirez et al (2007) and Lloyd (2008) found nectarivorous to be the most abundant guild of birds. Similarly, in the elfin forest of Yanachaga National Park (~ 90 km south-east of Carpish Mountains), Gonzalez (2008) found Diglossa and Metallura were the most abundant birds in the community.…”
Section: Introductionmentioning
confidence: 98%
“…Rodriguez-Flores et al 2012, Maglianesi et al 2014 and test specific hypotheses on the drivers of these interactions, such as morphological mismatch (Vinzentin-Bugoni et al 2014) or nectar quality and quantity (Maruyama et al 2014). An understudied ecosystem that has an abundant nectarivorous bird community occurs in the upper montane forest of the Andes (Ramirez et al 2007, Gonzalez 2008. In these forests, a diverse suite of hummingbirds and flowerpiercers is abundant (Gonzalez et al 2019).…”
Section: Introductionmentioning
confidence: 99%